Psychiatric and physical comorbidities and their impact on the course of bipolar disorder: A prospective, naturalistic 4‐year follow‐up study. (22nd May 2017) - Amann, Benedikt L; Radua, Joaquim; Wunsch, Christian; König, Barbara; Simhandl, Christian
Abstract : Objectives: The aim of the present study was to increase the available evidence on how physical and psychiatric comorbidities influence the long‐term outcome in bipolar I and II disorder. Methods: We examined the prevalence of comorbid physical (metabolic, cardiovascular, thyroid, and neurological) diseases and psychiatric (neurotic, stress‐related, somatoform, and personality) disorders and their impact on the risk of relapse in bipolar disorder. A total of 284 consecutively admitted patients with ICD‐10 bipolar I (n=161) and II (n=123) disorder were followed up naturalistically over a period of 4 years. Results: Globally, 22.0% patients had metabolic, 18.8% cardiovascular, 18.8% thyroid, and 7.6% neurological diseases; 15.5% had neurotic, stress‐related, and somatoform disorders; 12.0% had personality disorders; and 52.9% had nicotine dependence. We did not find any effect of comorbid metabolic, cardiovascular or neurological diseases or psychiatric disorders on the relapse risk. However, the presence of thyroid diseases, and especially hypothyroidism, was associated with an increased risk of manic relapse in bipolar disorder I (thyroid disease: hazard ratio [HR]=2.7; P =.003; hypothyroidism: HR=3.7;, P <.001). Among patients with hypothyroidism, higher blood levels of baseline thyroid‐stimulating hormone (bTSH) were also associated with an increased risk of manic relapse (HR=1.07 per milli‐international units per liter; P =.011), whereas blood levels of free triiodothyronine (fT3 ) or free thyroxine (fT4 ) were not found to have an influence. Conclusions: Our data underline the negative long‐term impact of thyroid diseases, and especially hypothyroidism with high blood levels of bTSH, on bipolar disorder with more manic episodes, and the importance of its detection and treatment.